The Aesthetics of Rock Music in Musical Drama Performances - Prima Suci Lestari; Syahrul Syah Sinaga; Suharto S; Udi Utomo; Eko Sugiarto (Universitas Negeri Semarang, 2024)
Drama is one of the components of theater education that can be integrated with other art forms. Within the various elements of theater or drama, there is a collaboration of visual arts, music, dance, drama, and literature. Popular music has been developing in Indonesia since the colonial era, particularly in the 20th century. During this period, genres such a Krontjong, Jazz, orchestral music, and rock music began to emerge. In the world of popular music, rock music has carved out its own space among enthusiasts, symbolizing freedom, rebellion, and high creativity, marked by its dynamic melodies and rhythms, as well as its profound lyrical content. Rock music has become a medium through which listeners express themselves. This article aims to elaborate on musical drama as a form of performance conducted by secondary school students, who take on the dual roles of actors and production team members, in exploring rock music through musical theatre. Such an approach enriches the students’ acting experiences within a musical context. Integrating rock music into the performing arts provides a fresh atmosphere that can influence the students’ characteristics and experiences. This study employs an exploratory qualitative method, involving various stakeholders, to analyze the implementation and impact not only to enhance students’ experiences in acting, but also to stimulate creativity by encouraging the analysis of rock music characteristics, which are expressed through drama. This process supports the development of diverse ideas in musical theatre, ultimately contributing to the quality and elements of school-based musical performance